2016
DOI: 10.1371/journal.pone.0167212
|View full text |Cite
|
Sign up to set email alerts
|

Gene-Based Genome-Wide Association Analysis in European and Asian Populations Identified Novel Genes for Rheumatoid Arthritis

Abstract: ObjectiveRheumatoid arthritis (RA) is a complex autoimmune disease. Using a gene-based association research strategy, the present study aims to detect unknown susceptibility to RA and to address the ethnic differences in genetic susceptibility to RA between European and Asian populations.MethodsGene-based association analyses were performed with KGG 2.5 by using publicly available large RA datasets (14,361 RA cases and 43,923 controls of European subjects, 4,873 RA cases and 17,642 controls of Asian Subjects).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 42 publications
(43 reference statements)
1
32
0
Order By: Relevance
“…Through a systematic review of published works, some authors identified some common HLA class II alleles that contribute to susceptibility to AIDs like RA in Americans an European populations [16]. In our study we observed associations of different HLADRB1 alleles with RA In Benin populations.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…Through a systematic review of published works, some authors identified some common HLA class II alleles that contribute to susceptibility to AIDs like RA in Americans an European populations [16]. In our study we observed associations of different HLADRB1 alleles with RA In Benin populations.…”
Section: Discussionsupporting
confidence: 59%
“…In Asian populations, the frequency was 6 and 5% and in the European populations it was 25.3% and 26.5% respectively [15]. These various studies reveal the very great variability of the HLADRB01 gene in the different populations [10,11,16]. However, in both the Asian and European populations the reported frequency was limited to some alleles of HLA DRB1 04 [16,17].…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations